What the Frak, Frankenstein!. Issue 2 (2015) - Thrall, James H.
<x content-type="archive" xml:space="preserve">Abstract</x> The SyFy television series Caprica (US, 2009-2010), prequel to the series Battlestar Galactica(US, 2004-2009), makes direct and oblique references to Mary Shelley's novel Frankenstein and its film adaptations, including especially James Whale's 1931 Frankenstein. These associations complicate the series' exploration of questions about the nature of life, death, and humanness; help position the created race of Cybernetic Life Form Nodes (Cylons) as simultaneously dangerous and sympathetic; rationalize religious experience in a manner resonant with Shelley's vision of a modern world without God; and support the postcolonial frame the series develops as it considers issues of power, gender, age, ethnicity, and class.